A 48-week randomized phase 2b study evaluating cenicriviroc versus efavirenz in treatment-naive HIV-infected adults with C-C chemokine receptor type 5-tropic virus. (27th March 2016) - Thompson, Melanie; Saag, Michael; DeJesus, Edwin; Gathe, Joseph; Lalezari, Jay; Landay, Alan L.; Cade, Jerry; Enejosa, Jeffrey; Lefebvre, Eric; Feinberg, Judith
Abstract : Objective: To compare the efficacy, safety, and anti-inflammatory effects of cenicriviroc (CVC), an oral, once-daily C-C chemokine receptor types 5 and 2 antagonist, with those of efavirenz (EFV) in treatment-naive, HIV-1-infected adults. Design: A 48-week, randomized, double-blind, double-dummy phase 2b trial at 43 institutions (USA and Puerto Rico). Methods: Study participants (HIV-1 RNA ≥1000 copies/ml, CD4 + cell count ≥200 cells/μl, C-C chemokine receptor type 5-tropic virus) were randomized 2 : 2 : 1 to CVC 100 mg (CVC100), CVC 200 mg (CVC200), or EFV 600 mg, each administered with emtricitabine/tenofovir disoproxil fumarate. Key end points were virologic success (HIV-1 RNA <50 copies/ml) at week 24 (primary) and week 48 (secondary), safety/tolerability at weeks 24 and 48. Study sites and patients remained blinded until week 48. Results: A total of 143 patients were randomized (CVC100, n = 59; CVC200, n = 56; EFV, n = 28). Virologic success was obtained at week 24 in 76, 73, and 71% of study participants for CVC100, CVC200, and EFV, respectively (all P > 0.05 versus EFV), and at week 48 in 68, 64, and 50%, respectively (all P > 0.05 versus EFV). Resistance mutations emerged in five and zero CVC and EFV-treated study participants, respectively. Virologic nonresponse and nucleoside reverse transcriptase inhibitor resistance decreased when CVC minimum plasma concentration was at least 47.8 ng/ml. Treatment-related adverse events of at least grade 2 and discontinuations because of adverse events were less frequent in CVC-treated study participants. Total and low-density lipoprotein cholesterol decreased with CVC, but increased with EFV. C-C chemokine ligand type 2 (CCL2) (aka monocyte chemotactic protein-1) increased in a dose-dependent manner, whereas soluble CD14 levels decreased with CVC. Conclusion: CVC showed efficacy and favorable safety in treatment-naive HIV-1-infected study participants, supporting selection of CVC200 for phase 3 studies. Trial registration: NCT01338883. Abstract : Supplemental Digital Content is available in the text